True Morels (Morchella Spp.) and Community Livelihood Improvement in Mankial Valley, District Swat, Khyber Pakhtunkhwa, Pakistan - Syed Fazal Baqi Kakakhel (Journal of Bioresource Management, 2020)
True morels collected from wild provide an economic source for the rural community of Mankial valley (District Swat, Khyber Pukhtunkhawa, Pakistan). Sale of approximately 334 kg in dry weight of five species of true morels (Morchella conica, M. esculenta, M. deliciosa, M. rotunda and M. semilibera) fetch US$ 57133 (under US$ 2015-16 exchange rate) to Mankial community and generate a revenue of US$ 62935 in Mingora (regional market) and US$ 87011 in Islamabad (national capital) markets. Morchella conica (average annual dry weight harvested 156 kg) has a high market price value (US$ 2964-44616) in all the three markets. M. esculenta (average annual dry weight harvested 120 kg) the second most harvested species (fetching US$ 20640-32040), M. deliciosa (34 kg; US$ 4216-6460), M. rotunda (13 kg; US$ 1482-2223) and M. semilibera (11 kg; US$ 1155-1672) appeared in decreasing order.